INNOVATIVE STRATEGIES FOR TEACHING PHYSICAL AND SPORTS SCIENCES IN KINDERGARTEN: AN EXPERIMENTAL APPROACH - Alessandro , R. Romano (Research Journal of Education and Allied Studies, 2024)
Kindergarten is the first educational environment, external to the family, in which each individual begins to relate to a group of peers. It is evident how important it is to lay the educational foundations in this context, so as to establish the basic conditions for training the future youth of tomorrow. In this perspective, the inclusion of experimental educational protocols in the educational curriculum of preschools could play a fundamental role. This Paper shows the application of an experimental educational protocol focused on motor and sports education, and analyzes the results in terms of educational growth and pedagogy compared to a control group that, instead, continued with regular school activities. The objective is to bring to light the educational benefits that an experimental motor and sports education approach is able to generate in children, and the extent to which training, starting from kindergarten, should be oriented in this direction